The treasury of Russian ancient musical written language (on the collection of singing manuscripts on the Book museum in SPSTL SB RAS) - T. G. Kazantseva (Библиосфера, 2010)
The collection of singing manuscripts in the Rare books and manuscripts department of SPSTL BS RAS, which is a unique collection of memorials of ancient Russian musical culture, is described.